2010
DOI: 10.1111/j.1537-2995.2010.02802.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood group genotyping by high‐throughput DNA analysis applied to 356 reagent red blood cell samples

Abstract: Systematic DNA analysis of panel donors should unquestionably change the management of reagent RBC selection. The notion of "antigens in double dose" should evolve regarding data obtained from DNA analysis, allowing an improved quality of reagent RBCs for antibody screening and identification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…In this study, the concordance rate between DNA‐based testing and serologic confirmation was 0.9997, similar to a 0.9995 concordance rate observed in a comparison of 356 reagent donor RBCs analyzed by hemagglutination and genotype using the same high‐throughput DNA platform used here . Fifty‐seven patients (11.5%) had at least one serologic discrepancy noted, compared to studies in multiply transfused patients with thalassemia and SCD that reported serologic and DNA‐predicted phenotype discrepancies in 36% to 51% of individuals .…”
Section: Discussionsupporting
confidence: 80%
“…In this study, the concordance rate between DNA‐based testing and serologic confirmation was 0.9997, similar to a 0.9995 concordance rate observed in a comparison of 356 reagent donor RBCs analyzed by hemagglutination and genotype using the same high‐throughput DNA platform used here . Fifty‐seven patients (11.5%) had at least one serologic discrepancy noted, compared to studies in multiply transfused patients with thalassemia and SCD that reported serologic and DNA‐predicted phenotype discrepancies in 36% to 51% of individuals .…”
Section: Discussionsupporting
confidence: 80%
“…This study revealed that genotyping using a microarray platform is a feasible blood group antigen genotyping tool that produces reliable data. The concordance rate with bidirectional sequencing was 100% and with serologic testing was 98·56%; these findings were in agreement with previous literature showing a 1% discrepancy rate, which could be attributed to the high rate of false‐positive results in serologic testing (Denomme & Oene, ; Kappler‐Gratias et al ., ; Bolye et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…The analysis of SMIM1 in Vel− subjects was conducted on historical blood samples that had been cryopreserved in the rare blood collection of the National Reference Center for Blood Groups (CNRGS, Paris, France) in order to establish the Vel− blood type of other subjects, and ultimately to identify the genetic basis of Vel− blood type. The analysis of SMIM1 in control Vel+ subjects was conducted on gDNA samples that had been extracted previously (Kappler‐Gratias et al, 2011). Fresh blood samples were obtained after informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA extraction from cryopreserved Vel− blood samples was performed with a QIAsymphony SP instrument and a QIAsymphony DNA Midi Kit (Qiagen) according to the manufacturer's instructions. Genomic DNA from control Vel+ regular blood donors had been extracted similarly (Kappler‐Gratias et al, 2011). DNA concentration was measured with a NanoDrop 2000c spectrophometer (Thermo Scientific).…”
Section: Methodsmentioning
confidence: 99%